Calcium renal lithiasis: metabolic diagnosis and medical treatment - Arrabal-Polo, Miguel Angel; Arrabal-Martin, Miguel; Garrido-Gomez, Juan (São Paulo Medical Journal, 2013)
Calcium renal lithiasis is a frequent condition that affects the worldwide population and has a high recurrence rate. Different metabolic changes may trigger the onset of calcium stone disorders, such as hypercalciuria, hyperoxaluria, hyperuricosuria, hypocitraturia and others. There are also other very prevalent disorders that are associated with calcium calculi, such as arterial hypertension, obesity and loss of bone mineral density. A correct diagnosis needs to be obtained through examining the serum and urinary parameters of mineral metabolism in order to carry out adequate prevention and treatment of this condition. Once the metabolic diagnosis is known, it is possible to establish dietary and pharmacological treatment that may enable monitoring of the disease and prevent recurrence of stone formation. Some advances in treating this pathological condition have been made, and these include use of sodium alendronate in patients with calcium renal lithiasis and osteopenia/osteoporosis, or use of a combination of a thiazide with a bisphosphonate. In summary, calcium renal lithiasis often requires multidrug treatment with strict control and follow-up of patients.